PELATIHAN PENCEGAHAN TINDAK PENIPUAN ONLINE DAN PERLINDUNGAN DATA PRIBADI KEPADA IBU-IBU PERWIRITAN DI TIBAN LAMA - Putri, Weni Lestari; Jarti, Nanda (PUAN INDONESIA, 2025)
This service is carried out to alert the public about the dangers of online fraud committed by irresponsible people. and how the solution that the service team does is to educate the public or to the mothers of the clerks who are in Tiban Lama. Namely about how to secure personal data to be safer from account hackers. in this service so that the mothers of the clerks are well educated. the service team hopes that the training held in Tiban Lama will be useful for the security of the mothers in the future. In the future, all levels of society will be more aware of online fraud and can secure their data and not be tempted by the lure of online fraudsters